Highlights of recent IFPRI food policy research for the European Commission 2016: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
EC financial support has helped to ensure that IFPRI’s research remains responsive, innovative, and effective in tackling the obstacles that stand in the way of achieving food security and poverty alleviation. Over the years, the EC’s support to IFPRI provided the necessary foundation for cuttingedge research in areas such as climate change; biofuels; and the nexus of agriculture, nutrition, and health. This support has helped IFPRI partner with strategic European partners in civil society, higher education, and public sector areas, with a focus on making food security research accessible through the development of global public goods, capacity-building networks, and technological platforms. In June 2015, IFPRI, the EC, and the German Ministry for Economic Cooperation and Development (BMZ) joined together to bring experts and stakeholders to discuss the latest thinking on sustainably improving livelihoods and welfare at a Brussels workshop, “Improving Food Systems for Better Lives.” The workshop highlighted the need for greater convergence among diverse actors, sectors, and stakeholders for the development and implementation of innovative solutions that will improve food systems and enhance food and nutrition security around the world.